Korelasi Profil Lipid dengan CK-MM terhadap Resiko Kejadian Penyakit Jantung Koroner pada Penderita Hipertensi Usia Produktif (Journal of Telenursing (JOTING), 2024)
This research is descriptive in nature with primary data from lipid profile and CK-MB examination results. The research method is observational with a cross sectional approach. The research sample was hypertensive patients at PKM in the city of Jambi with a sample of 50 people. The independent variable is lipid profile and the dependent variable is CK-MB. The results of the study showed that variables that had average levels above the normal value were cholesterol levels (211.43 mg/dl) where the value was normal (